Managing Diversity in Corporate America An Exploratory Analysis - Marquis, Jefferson P. (RAND Corporation, 2008)
Develops a fact-based approach to modeling diversity management in U.S. corporations, analyzes the strategies pursued by 14 large U.S. companies recognized for their diversity or human resource achievements, and compares a number of company characteristics. Firms recognized for diversity are distinguished by a core set of motives and practices, but best practices per se may not enable a company to achieve a high level of diversity.